Predictive Value of Susceptibility Vessel Sign for Arterial Recanalization and Clinical Improvement in Ischemic Stroke. Issue 2 (February 2019) - Darcourt, Jean; Withayasuk, Pattarawit; Vukasinovic, Ivan; Michelozzi, Caterina; Bellanger, Guillaume; Guenego, Adrien; Adam, Gilles; Roques, Margaux; Januel, Anne Christine; Tall, Philippe; Meyrignac, Olivier; Rousseau, Vanessa; et al.
Abstract : Background and Purpose—: Our goal was to evaluate whether the presence of a low signal intensity known as susceptibility vessel sign (SVS) on T2*-gradient echo imaging sequence was predictive of arterial recanalization and the early clinical improvement after mechanical thrombectomy. Methods—: This observational study was based on a prospective database of acute ischemic strokes treated by mechanical thrombectomy. Inclusion criteria were patients with acute anterior ischemic stroke, diagnosed by magnetic resonance imaging, including a T2*-gradient echo imaging sequence, and treated by mechanical thrombectomy. Two independent readers assessed the presence of an SVS. Successful recanalization was defined as a Thrombolysis in Cerebral Infarction score of 2b-3 after mechanical thrombectomy. Early clinical improvement was estimated by the difference between the baseline National Institutes of Health Stroke Scale and the National Institutes of Health Stroke Scale on day 1 after treatment Results—: The SVS was detected in 137 (76%) out of 180 patients. The kappa interrater agreement was 0.71 with a 95% CI of 0.59 to 0.82. Successful recanalization was associated with an SVS+ with odds ratio, 2.48; 95% CI, 1.05–5.74; P =0.03. The early clinical improvement was better in patients with an SVS+ (median, −6; interquartile range, −11 to 0) compared with SVS− patients (median, −1; interquartile range, −10 to 3) with P =0.01. Conclusions—: The visualization of SVS is a reliable and easily accessible predictive factor of recanalization success and early clinical improvement.